Perubahan Epidemiologi Demam Berdarah Dengue (DBD) di Indonesia Tahun 2017-2021 - Rezekieli Zebua; Vivian Eliyantho Gulo; Immanuel Purba; Malvin Jaya Kristian Gulo (Yayasan Literasi Sains Indonesia, 2023)
Epidemiology is a science that studies the distribution, frequency and determinants/factors that influence the incidence of disease or health problems in population groups. Epidemiology of infectious diseases can be caused by interactions between disease causes, hosts and the environment either directly or indirectly which can result in morbidity or death in groups of people/populations. Dengue Hemorrhagic Fever is an infectious disease caused by the Dengue virus and the Aedes aegypti mosquito as its main vector. Dengue Hemorrhagic Fever is characterized by the main clinical manifestations of high fever, hemorrhagic phenomena, often with hepatomegaly and in severe cases there are signs of circulatory failure. The purpose of this study is to determine changes in the epidemiology of Dengue Hemorrhagic Fever (DHF) in Indonesia in 2017-2021. This type of research is a quantitative descriptive research. The data used in this research is secondary data. Based on the research results, it is known that the epidemiological changes of dengue hemorrhagic fever (DHF) in Indonesia in 2017 were (26.10%), in 2018 there were (24.75%), in 2019 there were (51.53%), in 2020 there were (40 .0%) and in 2021 (27.0%). Based on the results of the data collected, the total number of provinces in Indonesia in 2017-2021 is 34 provinces. Based on the results of this study, it shows that changes and increases in Dengue Hemorrhagic Fever (DHF) increased dramatically in 2018 with an incidence rate of 51.53%.